Policy processes and food price crises: A framework for analysis and lessons from country studies - Babu, Suresh Chandra (Oxford University Press, 2015)
During the recent food crisis, developing countries responded with a wide variety of policy responses to protect their population. Understanding the policy-making process in developing countries is important to know how why such policy responses are made. In this chapter a framework is developed for analysing the policy process in developing countries and it is applied to study the food policy process during the food price crisis in selected countries. A synthesis of policy process analysis in 14 developing countries indicate that policy responses may differ depending on the nature and magnitude of roles actors in the policy process. Political institutions and organizational infrastructure for policy consultations, strategic analysis, knowledge management and monitoring, and timely warning of food crisis and its impact can determine the policy process and its outcomes. Several lessons for improving the policy process are derived from the country studies.